Analisis Perilaku Toke Kelapa Sawit Dalam Perspektif Etika Bisnis Islam Di Desa Bukit Indah kec. Muara Papalik Kab. Tanjung Jabung Barat - rizcatriutami; Ahsan Putra Hafiz; Puteri Anggi Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This thesis is entitled Analysis of Oil Palm Toke Behavior in the Perspective of Islamic Business Ethics in Bukit Indah Village, Kec. Muara Papalik Kab. Cape Jabung Barat. The method used in this research is descriptive qualitative. In collecting data, the authors used observation, interview and documentation methods. Based on the results of the research conducted, the results and conclusions were obtained: (1) The behavior of the oil palm toke in Bukit Indah Village admitted that they did not really understand good and correct Islamic business ethics. But in their daily life indirectly they have implemented it well, such as doing the five daily prayers properly even though this has not fulfilled the principles of business ethics in Islam. (2) Regarding the review of Islamic business ethics on the behavior of the oil palm toke in Bukit Indah Village, it is not fully in accordance with business ethics. Because basically the practice of buying and selling between toke and farmers already knows the ethics of doing business but in practice has not applied the principles. What is happening in this village is that there are still things that are considered detrimental to one party, for example in the non-transparent weighing mechanism, poor service, and determining the purchase price of palm oil. In terms of business ethics, this is contrary to the principles of Islamic business ethics, such as the principles of honesty, fairness and also the principle of trust. Then, with this research, it is hoped that further researchers will be able to carry out the material on the same Islamic business behavior in different ways of thinking. So that in the future it can be used as a reference for those who research in similar cases.